The Lexical Phrases Employed in The Thesis Abstracts of English Department Students - Agustinus Ngadiman (Widya Mandala Surabaya Catholic University, 2013)
Lexical phrases employed in the thesis abstracts of English Department students is the focus of the present study. The sources of the data were randomly selected from the thesis abstracts of the English Department students writing thesis for one of the requirements for the Bachelor degree. There are four kinds of lexical phrases employed :in students’ thesis abstracts; (a) verbal phrases, (c) noun phrases, (c) prepositional phrases, and others, typically longer clausal structures. The functions of those lexical phrases are (a) Reporting what other say, (b) Describing problems (c) Describing situation (d) Presenting results (e) Research and study aims (f) Expressing points of view (g) Expressing degrees of certainty (h) Presenting argument (i) connectors (j) Comparing and contrasting (k) Summering and (l) conclusion